Computer games and language learning - Ang, Chee Siang; Zaphiris, Panayiotis (My University, 2008)
The chapter discusses and examines the educational potential of computer games in language learning. The commercial success of games has recently attracted the scholarly study from various fields. However little has been done in term of learning theories despite the increasing interest in educational games. Thus, in this chapter, theoretical issues and practical challenges in game-based language learning are raised to provide an overview on the potential of gaming technologies for such purposes. Some prominent learning theories in relation to computer aided language learning are detailed. This is followed by a discussion of what computer games are before some case studies of game-based language learning are presented. Some implications on the language uses of computer games are derived and discussed.